Christians shaping identity from the Roman Empire to Byzantium : studies inspired by Pauline Allen - Dunn, Geoffrey D., 1962-; Mayer, Wendy, 1960-; Allen, Pauline, 1948- (Vigiliae Christianae, Supplements, 2015)
The essays collected in Christians Shaping Identity celebrate Pauline Allen's significant contribution to early Christian, late antique, and Byzantine studies, especially concerning bishops, heresy/orthodoxy and christology. Covering the period from earliest Christianity to middle Byzantium, the first eighteen essays explore the varied ways in which Christians constructed their own identity and that of the society around them. A final four essays explore the same theme within Roman Catholicism and oriental Christianity in the late 19th to 21st centuries, with particular attention to the subtle relationships between the shaping of the early Christian past and the moulding of Christian identity today. Among the many leading scholars represented are Averil Cameron and Elizabeth A. Clark.